An empathetic beginning in education: exploring the prospects of self-regulation skills on pro-social behaviour in the early childhood environment. Issue 4 (2nd April 2016) - Willis, Elizabeth
Abstract : One avenue substantially researched and supported in early childhood research is the importance and the cultivation of self-regulation skills in the classroom. Most educational research on self-regulation skills has illustrated the importance between the enhancement of these skills and long-term academic success. Notwithstanding, there is little empirical research in early childhood that links the advancement of self-regulation skills to other contributing educational components, such as the cultivation of children's pro-social skills. This review seeks to establish a link between children's self-regulation and pro-social skills and discusses implications for future research and practice.